Clinical characteristics and mutational analysis of the RyR2 gene in seven Czech families with catecholaminergic polymorphic ventricular tachycardia - Andrsova, Irena; Valaskova, Iveta; Kubus, Peter; Vit, Pavel; Gaillyova, Renata; Kadlecova, Jitka; Manouskova, Lenka; Novotny, Tomas (Pacing and clinical electrophysiology, 2012)
BACKGROUND: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare hereditary arrhythmia. The onset of clinical symptoms usually occurs during childhood, and is typically related to exercise. The aim of our study was to describe the clinical characteristics of seven Czech families with CPVT and the results of mutational analysis of the RyR2 gene in these families. METHODS: The subjects and their relatives were investigated at the participating departments. They underwent basic clinical investigation, and history was focused on possible CPVT symptoms, that is, syncopes during exercise. Bicycle ergometry was performed to obtain electrocardiogram recording during adrenergic stimulation. In all the investigated individuals, blood samples were taken for mutation analysis of the RyR2 gene. RESULTS: To date, seven families have been investigated, comprising 11 adults and 13 children. In seven CPVT patients, the indication for examination was syncope during exercise. Diagnosis was confirmed by bicycle ergometry-induced polymorphic ventricular tachycardia. In one relative, polymorphic ventricular tachycardia was also induced. All eight affected individuals were treated with β-blockers and in two, a cardioverter-defibrillator was implanted due to recurrent syncopi. Coding variants of the RyR2 gene were found in four probands. CONCLUSIONS: This is a systematic description of CPVT families in the Czech Republic. Our data support the importance of exercise testing for the diagnosis of CPVT. In addition, RyR2 gene coding variants were found in 50% of affected individuals.
Keywords: Polymorphism, Single Nucleotide; Humans; Ryanodine Receptor Calcium Release Channel; dítě; Child; jednonukleotidový polymorfismus; Female; mutace; mladý dospělý; dospělí; lidé; Adult; Pedigree; rodokmen; ženské pohlaví; Male; katecholaminergní polymorfní komorová tachykardie; genetická predispozice k nemoci; Genetic Predisposition to Disease; Czech Republic; Polymorphic Catecholaminergic Ventricular Tachycardia; Heterozygote; Young Adult; komorová tachykardie; heterozygot; Mutation; Česká republika; mužské pohlaví; ryanodinový receptor vápníkového kanálu; Tachycardia, Ventricular